(untitled) - Calder, Nigel (New York, 1979)
This brilliantly written book unlocks the astounding implications of Einstein's revolutionary theories on the nature of science, time and motion. It far surpasses any previous explanation of Relativity for laymen.
Keywords: Astrophysics,Relativity